Increasing the Efficiency of Transportation of Cargoes with a Cylindrical Shape - Mikhailov, Evgeny; Semenov, Stanislav; Kovtanets, Maxim; Dizo, Jan; Blatnicky, Miroslav; Ishchuk, Vadym (Communications - Scientific Letters of the University of Zilina, 2023)
One of the most important directions of intensification and increasing the efficiency of the transportation process is to improve the use of the carrying capacity and capacity of vehicles. For this, it is necessary to the choose rational schemes for loading the cargo into cargo places of the rolling stock. The possible options for loading the vehicle body with cylindrical loads, which are transported when they are installed on the end, are considered. The conducted analysis showed that there are several typical schemes for loading such cargoes. Analytical dependencies have been obtained that allow choosing a rational loading scheme when transporting such cylindrical loads, considering their parameters and the characteristics of cargo places of vehicles. Based on the performed research, the best variant is proposed, i.e. the option with the clearance of 0.2 m, allowing transportation of 125 cylindrical cargo units in the space of a vehicle.
Keywords: transportation cylinder shape cargo diameter vehicle body loading scheme optimization